Ten Year Results of a Fibromyalgia Out-Patient Clinic: Is There a Happy Ending? - Burcu YANIK,; Derya GÖKMEN,; Ümit SARP,; Yeşim KURTAİŞ AYTÜR,; Süreyya ERGİN, (Archives of Rheumatology, 2011)
Objectives: In this retrospective cohort, we determined the clinical characteristics, treatment options and outcomes of fibromyalgia syndrome (FMS) patients and reported the results of the 10 years of experience of our Fibromyalgia Follow-up Outpatient Clinic (FOC). Patients and methods: Of the 308 patients (247 females, 61 males) who were referred to the FOC with suspicion of FMS, 252 were diagnosed with FMS. The demographic data of all patients were recorded. The patient forms of the FOC were used to question whether the patients had widespread body pain, fatigue, sleep disorders, morning stiffness, paresthesia, Raynaud's phenomenon, dry eye, dry mouth, irritable bowel syndrome, headaches, decreased libido, symptoms of female urethral syndrome, or subjective swelling. The level of pain intensity, presence of a sleep disorder, number of tender points, total myalgic score, the fibromyalgia impact questionnaire (FIQ), the health assessment questionnaire (HAQ) and Beck depression inventory (BDI) were also recorded after each visit done in three or six month intervals. All the recorded data were analyzed taking into consideration missing data. Results: The disease duration, number of tender points, total myalgic score (p<0.001), HAQ-total, headache, paresthesia, sleep disorders, morning stiffness, reduction in libido and irritable bowel syndrome (p<0.05) showed a statistically significant difference between FMS (+) and FMS (–) patients. The clinical parameters of the number of days in a week the patient had difficulty falling asleep (sleep-1), total myalgic score, FIQ-total and HAQ-total scores in FMS (+) patients showed significant changes over time. The FIQ-total and pain improved significantly in patients who had been administered selective serotonin re-uptake inhibitor drugs (p<0.05). The FMS (+) patients who were treated with amitriptyline showed significant improvement in sleep-1: however, no significant difference was detected in clinical parameters of the patients taking sertraline. Conclusion: Since FMS is a musculoskeletal disorder with a wide variety of clinical signs and symptoms, it is essential to evaluate every patient individually according to predominant clinical features in order to apply the best treatment. Dividing these patients into subgroups may be useful.